Development of an Imtaq Project-Based Program to Enhance Early Childhood Faith and Piety - Sauqy, Dzulfikar; Susilawati, Ulfah; Pratiwi, Indy Ari (Jurnal Pendidikan Anak, 2025)
The suboptimal implementation of religious and moral values in early childhood learning has created a gap between curriculum planning and classroom practice. This study aims to develop an "Imtaq" (Faith and Piety) project-based learning program designed to strengthen religious and moral values in early childhood education. The research involved 48 early childhood learners and four teachers from RA Matholiul Ulum and BA Danurejo 1. The study employed the ADDIE Development model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. During the Development stage, expert validation was conducted by two specialists in Early Childhood Education and learning program Development. The validation results were analysed using descriptive statistics and a paired-samples t-test. The findings indicated that the calculated t-value was 3.408, while the Sig. (2-tailed) The value was 0.001, which is lower than 0.05. This demonstrates that the program effectively integrates core religious values such as honesty, tolerance, and empathy into children's daily learning experiences. Overall, the results indicate that project-based learning centred on faith and devotion can strengthen children's religious concepts while fostering the comprehensive Development of religious and moral values